Critical Thinking and Philosophy : A Dialogue with New Tunes - Suárez González, Javier Roberto; Pabón Llinás, Daniela; Villaveces Franco, Leonor; Martín Gallego, Julio Antonio (Barranquilla, Colombia : Editorial Universidad del Norte, 2020)
En el desarrollo de este trabajo los autores logran entablar un exitoso diálogo polifónico sobre el desarrollo del pensamiento crítico en el proceso de aprendizaje de los estudiantes, con enfoques teóricos provenientes de diversas disciplinas, así como con distintas tradiciones de la filosofía moderna y contemporánea. La obra también se encuentra traducida en idioma inglés.
Legal -- Table of Contents -- Introduction -- Prologue -- THE RESEARCH PROJECT -- Critical Thinking in the Classroom as a Tool for Ethical Action in a Public World -- 1. Transdisciplinary Approaches on Critical Thinking -- 1.1 Critical Thinking from a Cognitive Perspective -- 1.2 "Hermeneutics" and Critical Thinking in Latin America -- 1.3 Critical Thinking as Constructive Thinking -- 1.4 An Integrated Theory -- 2. Philosophical Perspectives on Critical Thinking -- 2.1 A Critique of Critical Thinking -- 2.2 The Reflective Judgment and the Inclination towards Public-Political Reason -- 2.3 Reflective Thinking as a Synonym for Critical Thinking -- 2.4 Thought and Social Reflexivity -- 2.5 The Practical Implications of Critical Thinking -- 3. Practical Areas of Critical Thinking: Ethics and Education -- 3.1 Critical Education as a Public Issue -- 3.2 Education as Critical Self-Reflection -- 3.3 Education and Experience [Erfahrung] -- 3.4 Critical Education for Global Citizenship -- 3.5 Critical and Ethical Thought -- 4. "Thinking Critically to Live": The Categories of the Sensitive as a Conceptually New Proposal -- 4.1 The Importance of "Relationality" and Dialogue -- 4.2 The Importance of Embodied and Affective Thinking -- 4.3 The Importance of Reflective Thinking -- 4.4 Categories of the Sensitive -- 4.5 Critical Thinking as a Lifestyle -- 5. Critical Thinking in the Classroom: A Dialogue on the Public Policies of Teaching Philosophy -- 5.1 Methodological Notes -- 5.2 Empirical Results -- 5.3 Workshops with Teachers -- 5.4 Institutional Policies and Public Guidelines Regarding Critical Thinking -- 5.5 Empirical Data Contributions on the Notions of Critical Thinking: A Diagnosis Based on Current Reality -- 6. Critical Thinking and Ethical Decision-Making in a Public World -- References -- Annexes -- About the Authors.
Incluye referencias bibliográficas (páginas 79-82).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Philosophy; Critical thinking; Pensamiento crítico.; Filosofía de la Educación.; Educación moral; Moral education; Libros electrónicos.